Sasi Laut as a Culture of Natural Resources Conservation to Overcome the Tragedy of the Commons in Maluku Province - Muin, Abdul; Rakuasa, Heinrich (PT. Riset Press International, 2023)
This research focuses on the cultural practice of conservation known as